A CLINICOPATHOLOGICAL STUDY OF LESIONS OF BONE - Bhuva, Kaushik; Vachhani, Anand; Parmar, Paritosh; PATEL, DIPMALA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to study the clinico-pathological diagnosis of bone lesions. Methods: The present study was a prospective and observational (non-interventional) type of study. A total of 100 patients from March 2012 to April 2013 were recruited. All excised bone specimens received in the Department of Pathology, SBKS MI and RC, Pipariya, constituted the study material. The specimens were subjected to a detailed histopathological examination. In each case, the pathological reaction pattern was studied carefully and documented. Results: The total number of cases studied was one hundred, of which 63 were males and 37 were females in the age group of 3 years–65 years. The most common presenting symptoms were pain and swelling in all bone lesions. Out of 100 cases, non-neoplastic cases were 54% and neoplastic cases were 46%. Among 46% of neoplastic lesions, we found that 30% were benign and 16% were malignant. Among non-neoplastic lesions, 14% were tumor-like lesions, 13% were non-specific osteomyelitis, 12% were tuberculosis inflammation, and 15% were avascular necrosis. The most common benign lesion was a giant cell tumor (17%). The most common malignant lesion was osteosarcoma (6%). The most common tumor-like lesion was fibrous dysplasia (9%). The majority of bone tumors were located in the epiphysis of long bones. Conclusion: Light microscopy or histopathological examination is the gold standard in the diagnosis of bone lesions and is invariably accurate when correlated with clinico-radiological features.